PENGEMBANGAN MEDIA INTERAKTIF WORDWALL TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS KELAS IV SDN BABAKANJATI: Penelitian Skripsi - Rifa Tri Khairunnisa; Nana Sutarna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Development of Interactive Wordwall Media on Students' Critical Thinking Skills in Science Subject, Grade IV SDN Babakanjati. Elementary School Teacher Education Study Program (PGSD), 2025. The purpose of this study is to develop interactive wordwall media and also to determine the effectiveness of interactive wordwall media seen from whether there is an increase in students' critical thinking skills after using interactive wordwall media. This study was conducted in grade IV SDN Babakanjati with a sample of 20 students. The research method is Research and Development (R&D) with the Borg and Gall design which has been simplified by Prof. Dr. Nana Syaodih Sukmadinata (2010), the stages passed include: (1) Preliminary Study which includes literature study and field survey; (2) Media Development which includes needs analysis, media design and expert validation, limited trials conducted at SDN Karangmangu with a sample of 15 students, extensive trials conducted at SDN Karangsari with a sample of IV A 20 students and IV B 21 students; (3) Effectiveness Test which includes pretest, treatment, posttest, and final media. After implementation, there are results before and after implementation where the results show that the Pretest results have an average value of 54.1 and the Posttest results have an average value of 83.75. After being given treatment and shows that the Sig. value (2-tailed) = 0.000 <0.05. This means that there is an increase before and after using interactive wordwall media. And the effectiveness of the media is known based on the N Gain test which obtained a value of 66.57% in the fairly effective category.